Greek κόμμι: Its Ultimate Origin and Implications for Afro-Asiatic Prehistory - Takács, Gábor (Polskie Towarzystwo Filologiczne, 2022)
In this paper2, two decades after my first attempt3 at examining this etymological puzzle, I attempt to trace down the ultimate etymology of the Greek-Latin term, the source of our European word for ‘gum’, whose well-known Egyptian etymon is qmj.t ‘gum’ (attested from the New Kingdom on). But how it comes from a supposed heritage of the underlying proto-language has so far been unknown aside from the single isolated West Chadic cognate I had suggested some 20 years ago. Since then, having carried on my extensive comparative research on the supposed common Afro-Asiatic lexical root stock, I keep assuming this Egyptian word to only have cognates in West Chadic, at the moment in three diverse groups of it. In this new study, I not merely attempt at demonstrating the regularity of the consonant correspondences in question by adducing several relevant examples from the etymological material, but also try to define the place of this exclusive Egypto-Chadic isogloss in the history of the common Afro-Asiatic root stock and in the Holocene prehistory of the first known neolithic language family on earth.